2021
DOI: 10.3390/biology10111106
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Dependent Oligomerization of Thermus thermophilus Trigger Factor Chaperone

Abstract: Thermus thermophilus trigger factor (TtTF) is a zinc-dependent molecular chaperone whose folding-arrest activity is regulated by Zn2+. However, little is known about the mechanism of zinc-dependent regulation of the TtTF activity. Here we exploit in vitro biophysical experiments to investigate zinc-binding, the oligomeric state, the secondary structure, and the thermal stability of TtTF in the absence and presence of Zn2+. The data show that full-length TtTF binds Zn2+, but the isolated domains and tandem doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…More recently, the kinetics–activity relationship has been supported by a study on TF monomer and dimer, and it has been proposed that kinetic modulation of chaperones can be coupled with the oligomerization of molecular chaperones [ 13 , 67 ]. Although further investigation is needed, it has been proposed that the assembly of client-binding sites after molecular chaperone oligomerization increases the association rate between the client protein and chaperone [ 13 ].…”
Section: Kinetic Studies For Molecular Chaperones and Client Proteinsmentioning
confidence: 99%
“…More recently, the kinetics–activity relationship has been supported by a study on TF monomer and dimer, and it has been proposed that kinetic modulation of chaperones can be coupled with the oligomerization of molecular chaperones [ 13 , 67 ]. Although further investigation is needed, it has been proposed that the assembly of client-binding sites after molecular chaperone oligomerization increases the association rate between the client protein and chaperone [ 13 ].…”
Section: Kinetic Studies For Molecular Chaperones and Client Proteinsmentioning
confidence: 99%
“…Activity modulation coupled with oligomerization is also seen for the TF in Thermus thermophilus (TtTF), which is activated through zinc-induced oligomerization. 66,67 The in vitro biochemical study identied that the zinc activates the holdase activity of TtTF, in which the refolding of green uorescent protein (GFP) was arrested in the presence of TtTF and zinc ions. 67 The subsequent study identied that zinc binding capacity is specic to TtTF among the tested TF species from Thermus thermophilus, Thermotoga maritima, and Escherichia coli.…”
Section: Functional Importance Of Oligomerization Of Molecular Chaper...mentioning
confidence: 99%
“… 67 The subsequent study identified that zinc binding capacity is specific to Tt TF among the tested TF species from Thermus thermophilus , Thermotoga maritima , and Escherichia coli. 66 Although the detailed mechanism remained to be elucidated, the study unveiled that zinc binding induces a change in the secondary structures and oligomerization of Tt TF. Activity modulation coupled with oligomerization has been reported not only for TF but also other molecular chaperones, including Skp, 68 HSP16.6 from the cyanobacterium Synechocystis , 69 and DNAJB6.…”
Section: Unraveling the Mechanism Of Protein Folding And Holding By M...mentioning
confidence: 99%